Parameters derived from the generalized kinetic and distributed parameter models: a perfusion CT study - Li, T. H. (2013)
Dynamic contrast-enhanced (DCE) imaging is a functional imaging technique that can be used to assess tumor angiogenesis and yields quantitative estimates of tissue microcirculatory parameters by tracer kinetic model analysis. In this study, we explored the possible relationships between parameters of two tracer kinetic models, the generalized kinetic and distributed parameter models, by comparing these models on DCE CT datasets of actual patient study cases. Understanding the use of these models and the physiological meaning of their parameters would improve the interpretation and assessment of anti-angiogenic drug trials by DCE imaging.